THE IMPACT OF HEAT EMISSIONS FROM LIGHT GASOLINE VEHICLES ON URBAN MICROCLIMATE AND AIR TEMPERATURE: AN EXPERIMENTAL AND MODELING ANALYSIS (Web of Technology: Multidimensional Research Journal, 2025)
This study investigates the impact of heat emissions from light gasoline vehicles on urban microclimate and air temperature. Using both experimental measurements and computer modeling, the effect of vehicle-generated heat on ambient air temperature was analyzed. The results provide insights into the contribution of automobiles to urban heat load and offer recommendations for improving urban microclimate management.